The Correlation between Second Stage (Childbearing) Family Development Task with Completeness of Polio Immunization in Working Area of Wara Utara KotaPublic Health Center in 2018 - Ratnasari Iskandar; Nur Aspina R Djano; Rahmah Tahir (Journal of Health Science and Prevention, 2019)
Background: The second stage of family development refers to the stage when a baby was born in a family of new couples. The second phase of the family starts from the birth of the first child until the baby becomes months old. This stage has a health concern in the fulfillment of its development task; namely, a type of primary immunization that is Polio immunization given completely in infants aged 1 - 4 months old. Objective: to know the correlation of family development second stage task (childbearing family) with the of Polio immunization in infants in the Area of Wara Utara KotaPublic Health Centers in 2018. Method: This research used cross-sectional analytical correlation emphasizing on the time of measurement/observation of independent and dependent variable data assessed on a one time simultaneous basis. The population of this research was families with second stage . The sample was 74 people a purposive sampling method. Data analysis by Chi-Square test. Results: The result of statistical analysis resulted in = 0,002 <Î± = 0,05, so there was a correlation between family development task with the of Polio immunization. Conclusion: Second stage family development task is the transition stage of the individual role, become parents/a parent and form a permanent system. This stage has attention health in fulfilling tasks development, especially Immunization.